1978
DOI: 10.1002/jez.1402050116
|View full text |Cite
|
Sign up to set email alerts
|

Inositol pentaphosphate in fish red blood cells

Abstract: Inositol pentaphosphate (IP5) has long been characteristic of avian erythrocytes. We now report that this compound is also present in the red cells of two species of elasmobranch fishes, Squalus acanthias (spiny dogfish) and Narcacion nobiliana (torpedo ray). The mean concentration of I5 is 0.36 and 0.24 micromoles per ml of red cells respectively. ATP is the major organic phosphate in both fishes. 2.3-diphosphoglycerate is absent and GTP levels correspond approximately to the levels of I5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This latter compound is effective in causing a right shift of the oxygen equilibrium of fetal-and adult-type duck hemoglobins (Borgese and Nagel, 1977). Borgese and Nagel (1978) recently reported that inositol pentaphosphate is also present in the red cells of two species of elasmobranch fish and suggested that it may play a role in regulating the oxygen affinity of dogfish and torpedo hemoglobins. Inositol tetraphosphate is the major organic phosphate in erythrocytes of the adult ostrich (Isaacks et at., 1977).…”
Section: Function Of Inositol Phosphatesmentioning
confidence: 97%
See 1 more Smart Citation
“…This latter compound is effective in causing a right shift of the oxygen equilibrium of fetal-and adult-type duck hemoglobins (Borgese and Nagel, 1977). Borgese and Nagel (1978) recently reported that inositol pentaphosphate is also present in the red cells of two species of elasmobranch fish and suggested that it may play a role in regulating the oxygen affinity of dogfish and torpedo hemoglobins. Inositol tetraphosphate is the major organic phosphate in erythrocytes of the adult ostrich (Isaacks et at., 1977).…”
Section: Function Of Inositol Phosphatesmentioning
confidence: 97%
“…Inositol pentaphosphate has long been recognized as a predominant organic phosphate in the erythrocytes of most avian species (Johnson and Tate, 1969). This compound has also recently been characterized in the red cells of two species of elasmobranch fish-the spiny dogfish and torpedo ray (Borgese and Nagel, 1978). In contrast, the erythrocyte of the adult ostrich contains inositol tetraphosphate as the major organic phosphate (Isaacks et ai., 1977).…”
Section: Inositol and Its Biological Formsmentioning
confidence: 97%
“…For example: 2,3-bisphosphoglycerate (Z,3-P2 -glycerate) previously considered a characteristic only of mammalian erythrocytes, has been observed as a major constituent of the red cells of embryos of birds and reptiles and in the red cells of the armored catfish (Borgese and Lampert 1975;Harkness 1975, 1980); inositol tetrakisphosphate (inositol-P4 ) was found to be the major organic phosphate in erythrocytes of the mature ostrich (Isaacks and Harkness 1980); inositol pentakisphosphate (inositol-Ps) previously considered a characteristic of avian erythrocytes has been observed in erythrocytes of several species of fishes and sea turtles (Bartlett 1980;Borgese and Nagel 1978;Isaacks and Harkness 1980;Rapoport and Guest 1941); inositol bisphosphate (inositol-P2 ) has been found in erythrocytes of the South American (Lepidosiren paradoxa) and African (Protopterus aethiopicus) lungfish (Bartlett 1980;Isaacks and Harkness 1980), but its role as a modifier of hemoglobin function has not been verified; and in some of our very recent studies the red blood cells of monotremes, the egg-laying mammals (echidna and duckbill platypus), were found nearly devoid of adenosine triphosphate (ATP) (Kim et al 1981;Isaacks et al 1984), only traces were present (0.03 and 0.06 roM, respectively).…”
Section: Introductionmentioning
confidence: 96%